Pengembangan Tes Diagnostik Esai Terstruktur Kimia Materi Titrasi Asam Basa Sebagai Instrumen Analisis Hasil Belajar Siswa - Crismonia Rinta; Zonalia Fitriza (Universitas Negeri Padang, 2022)
Learning difficulties experienced by students in a subject can affect their learning outcomes. Learning difficulties can be caused by misconceptions experienced by students or knowledge barriers. It can be happened because chemistry has complex materials which require students to comprehend prerequisite concepts before mastering complex concepts. This research aims to develop a Structured Essay Diagnostic Test of Chemistry for acid-base titration material that fulfils good criteria as an instrument for identifying misconceptions, learning barriers, and assessing student learning outcomes. The research procedure consists of 3 stages: determining the content, obtaining information about students misconceptions, and developing a diagnostic test. The SEDToC instrument was tested for validity and reliability. The SEDToC was validated by four educational chemists and high school chemistry teachers. Which was concluded that the SEDToC instrument is valid, and reliable in the very high category. Analysis of the difficulty index of the SEDToC instrument obtained 10 items in the easy category and 18 questions in the difficult category. The analysis of the discriminatory power of the questions was obtained that 6 items were in a bad category, 18 questions were in the sufficient category, three item was in a good category and one item was in a very good category. The results of the study using the SEDToC instrument for acid-base titration materials proved that the SEDToC instrument was able to assess student learning outcomes, identify misconceptions, and material inhibiting students.